Bones and all [videorecording (Blu-Ray)] - Kajganich, David, 1969-; Chalamet, Timothée; Russell, Taylor, 1994-; Stuhlbarg, Michael; Holland, André; Sevigny, Chloë; Green, David Gordon, 1975-; Harper, Jessica; Horowitz, Jake; Rylance, Mark; Khachaturan, Arseni, 1993-; Reznor, Trent; et al. (Metro-Goldwyn-Mayer Pictures Inc., 2022)
A story of first love between Maren, a young woman learning how to survive on the margins of society, and Lee, an intense and disenfranchised drifter. It's a liberating road odyssey of two young people coming into their own, searching for identity and chasing beauty in a perilous world that cannot abide who they are.